Cistite bacteriana e fúngica assintomática em cadela diabética - Relato de caso - Adams, Felipe Kunz [UNESP]; De Vasconcellos, Amanda Leal [UNESP]; Galvão, André Luiz Baptista [UNESP]; Costa, Mirela Tinucci [UNESP]; Carvalho, Marileda Bonafim [UNESP] (My University, 2013)
This is a case report of a poodle bitch, 10 years-old, weighting 5.5 kg, was examined for diabetes mellitus and mitral endocardiosis control. The patient did not show any lower urinary tract sign, however, the urinary sedimentoscopy revealed the presence of bacteria, leukocytes, erythrocytes, pseudo-hyphae and yeast. The urine cultures resulted in growth of countless colonies of Escherichia coli and Candida spp.
Bacterial and fungal asymptomatic cystitis in diabetic bitch - Case report
Keywords: Candida spp.; Dog; Endocrinopathy; Escherichia coli